Choice and success of job search methods - Andrea Weber; Helmut Mahringer (Institute for Advanced Studies (IHS), 2002)
Job seekers can influence the arrival rate of job offers by the choice of search effort and the search methods they use. In this paper we empirically investigate the contribution of the use of different search methods on the outcome of search. Using unique data on the search behaviour of job seekers sampled from the inflow into employment during the year 1997 in Austria we analyse the quality of job matches in terms of wages and job durations. We find evidence for endogenous selection to the job matching channels. Persons with few social contacts or lower unobserved ability are more likely to be matched by the public employment service. Hence we conclude that selection may contribute to the unfavourable wage outcomes for jobs generated by the public employment service.
Keywords: J20; J64; C31; 330; job search; search channels; selectivity bias; Arbeitsuche; Erfolgsfaktor; Arbeitsvermittlung; Soziale Beziehungen; Schätzung; Österreich